2023
DOI: 10.1186/s12912-023-01191-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to nurses’ therapeutic communication practices in a district hospital in Ghana

Abstract: Background Patients accessing health care enter the hospital environment with extreme anxiety, fear and distress which impacts their interactions with nurses and other health care professionals who are expected to help allay these anxieties in order to enhance patients care satisfaction. However, evidence suggests that there is a lack of effective therapeutic nurse-patient interaction in hospitals and the clinical environment globally, especially in sub-Saharan Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
0
0
3
Order By: Relevance
“…This aligns with the research of Amoah et al, which identified a low number of nurses and high workload as obstacles to effective communication between nurses and patients (14). Similarly, Appiah et al (2023) highlighted increased workload and stress as barriers to nurse-patient communication (20).…”
Section: Discussionsupporting
confidence: 84%
“…This aligns with the research of Amoah et al, which identified a low number of nurses and high workload as obstacles to effective communication between nurses and patients (14). Similarly, Appiah et al (2023) highlighted increased workload and stress as barriers to nurse-patient communication (20).…”
Section: Discussionsupporting
confidence: 84%
“…Il est important de souligner que la satisfaction des patients et les expériences positives sont des éléments clés pour obtenir de meilleurs résultats en matière de traitement. Des études ont montré que la communication thérapeutique de qualité est liée à la satisfaction des patients et à des expériences agréables (Appiah et al, 2023). Une communication claire et efficace entre un médecin et son patient est un aspect essentiel de la pratique médicale.…”
Section: Introductionunclassified
“…Toutefois, une proportion non négligeable (38,8%) révèle n'avoir pas communiqué régulièrement avec les soignants. Selon les données de la littérature, il semblerait qu'il y ait un déficit d'interaction thérapeutique efficace entre l'infirmière et le patient dans les hôpitaux et les environnements cliniques à travers le monde, en particulier en Afrique subsaharienne(Appiah et al, 2023). La communication entre un professionnel de santé et un patient apparaît comme un élément fondamental de la relation de soin.…”
unclassified
See 1 more Smart Citation